Integrity versus Intervention Boundaries in Modernist Housing Complexes: Case study of the healt/holiday districts in Ustroń - Ciarkowski, Błażej (Protection of Cultural Heritage, 2021)
The aim of this article is to analyze the contemporary situation of post-war modernist building complexes located in the natural landscape of extraordinary values and to distinguish potential opportunities and threats for the future. The analysis was made as a case study of two extraordinary complexes: Ustroń-Zawodzie health district and Ustroń-Jaszowiec holiday district. Modernist leisure districts are an example of complex urbanist-architectural projects including modern architecture of significant social value adjusted (scale, technology, form) to the natural conditions and built with due regard for the value of the landscape (in the spirit of the modern movement). Their preservation should go beyond the scale of a single architectural object and start from the point where the health-leisure district are considered as a cultural landscape.